Depression and Intolerance of Uncertainty: Association with Decisional Conflict in Otolaryngology Patients. (March 2022) - Cleveland, Chelsea; Newby, Maxwell; Steinman, Shari; Wanstreet, Tyler; Callaham, Sarah; Razdan, Reena; Coutras, Steven; Patel, Rusha; Carr, Michele M.
Objective: To determine if anxiety, stress, depression, worry, and intolerance of uncertainty were related to pre-operative decisional conflict (DC), shared decision making (SDM), or demographic variables in adult otolaryngology surgical patients. Methods: Consecutive adult patients meeting criteria for otolaryngological surgery were recruited and completed DC and SDM scales, Penn State Worry Questionnaire (PSWQ), Intolerance of Uncertainty Scale (IUS-12), and Depression, Anxiety and Stress Scale-21 (DASS-21). Results: The cohort included 118 patients, 61 (51.7%) males and 57 (48.3%) females. Surgery was planned for a benign process in 90 (76.3%) and 46 (39.3%) had previous otolaryngologic surgery. SDM and DC scores did not significantly differ across gender, age, education level, previous otolaryngologic surgery or whether or not surgery was for malignancy. Patients with no malignancy had significantly higher DASS-21 Stress scores (mean 12.94 vs 8.15, P < .05) and total IUS-12 scores (mean 28.63 vs 25.56, P = .004). Women had lower PSWQ scores (41.56 vs 50.87 for men, P = .006). IUS-12 and PSWQ declined with age. DC scores correlated positively with DASS-21 Depression ( r = .256, P = .008) and IUS-12 scores ( r = .214, P = .024). SDM correlated negatively with DASS-21 Depression ( r = −.208, P = .030). Linear regression model for DC scores revealed a significant relationship with DASS depression ( B = 0.674, P = .048). Conclusion: Preoperative decisional conflict is associated with increased depression and intolerance of uncertainty in adults undergoing otolaryngologic surgery. Screening for and management of depression, anxiety, and related concerns may improve surgical outcomes in this group.